Internalized Stigma and Associated Factors among Patients with Major Depressive Disorder at the Outpatient Department of Amanuel Mental Specialized Hospital, Addis Ababa, Ethiopia, 2019: A Cross-Sectional Study. (17th August 2020) - Alemayehu, Yadeta; Demilew, Demeke; Asfaw, Getachew; Asfaw, Henock; Alemnew, Nigus; Tadesse, Agitu
Abstract : Background . Internalized stigma has been found to be widespread among patients with major depressive disorder. When internalized stigma exists in patients with depression at a high level, it worsens the treatment outcome and quality of life. So the aim of the study is to assess the magnitude of internalized stigma and associated factors among outpatients with major depressive disorder at Amanuel Mental Specialized Hospital, Addis Ababa, Ethiopia. Methods and Materials . An institutional-based cross-sectional study was conducted among 415 respondents from May 6 to June 13, 2019. Internalized stigma was assessed by using the internalized stigma of mental illness scale. Data was entered to Epi-data version 3.1 and analyzed using SPSS version 20. Bivariable and multivariable binary logistic analysis was done, and p values less than 0.05 were considered statistically significant with 95% CI. Results . The prevalence of high internalized stigma among patients with major depressive disorder was 33.5% (95% CI: 29.2, 38.3). Being single (AOR = 2.54, 95% CI: 1.30, 4.95), having an illness greater than or equal to 2 years of duration (AOR = 3.21, 95% CI: 1.66, 6.19), history of suicidal attempt (AOR = 2.33, 95% CI: 1.35, 3.99), nonadherence to treatment (AOR = 2.93, 95% CI: 1.62, 5.29), poor social support (AOR = 4.72, 95% CI: 2.09, 10.64), and poor quality of life (AOR = 3.16, 95% CI: 1.82, 5.49) were significantly associated with high internalized stigma at p value < 0.05. Conclusion . The magnitude of internalized stigma was high among patients with major depressive disorder. Reduction of internalized stigma through antistigma campaigns and supports given to patients at the earliest possible time is important to improve treatment outcome and quality of life and minimize suicidal behavior in patients with major depressive disorder.